To what extent is the readiness of AADK’s clients to join workforce? A case study at CCVC and CCRC Sepang, Malaysia - Noh Amit; Rozmi Ismail; Norhayati Ibrahim; Muhammad Ajib Abd Razak; Faizah Isa; Abdul Halim Mohd Hussin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Securing a job in life of recovering substance users is important as an employment enables them to financially contribute to society, personal life and family members. Before joining the labor workforce, recovering substance users as pontential employees need to ensure that their skills meet the needs of today's job marketplace. The objective of this study is to determine the aspects of readiness among clients of Agensi Anti dadah Kebangsaan (AADK) who are undergoing rehabilitation at Cure and Care Vocational Center (CCVC) and Cure and Care Rehabilitation Center (CCRC) Sepang before joining the employment workforce. A total of 257 respondents who are clients of AADK rehabilitation centers were involved in this study. The results indicate that the majority of clients show moderate levels of communication skills, professional skills and soft skills. However, there is a high level of willingness/readiness to increase knowledge, ability to deal with work situations and motivation to work. The findings also found that there was a positive and significant relationship between communication skills, professionalism, softskills, willingness/readiness to acquire knowledge, ability and motivation to work. Meanwhile, there is a significant difference between the CCVC and CCRC client's in willingness/readiness to work. Regression analysis showed that the knowledge and ability variables are the best predictors of client motivation to work. The results of this study can offer input to the AADK to improve the content of the modules and interventions in order to holistically strengthening the client's willingness/readiness to secure jobs in the future.